Studi Komparasi Self Control Siswa yang Memiliki Kecerdasan Spiritual Tinggi dan Rendah di Kelas XII SMAN I Kota Kediri Tahun Pelajaran 2013/2014 - Ady Alfan Mahmudinata (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2016)
Referring to the character of the Education Act in Indonesia listed in Act 20 of 2003 on National Education System Indonesia Article: 1 The purpose of national education to develop the potential of learners to have the intelligence, personality, and noble character; and article 3, paragraph 1: National education serves to develop the ability and shape the character and civilization of the nation's dignity in the context of national life as well as you view the proyeksitas Islamic religious education that is feeding religious spiritual student-related non- Islamic values are synergistic against strong self control gaining control himself strong for the students, for the writer interested to learn and find out about the intelligence level of spiritual and differences self Control students, among students who have spiritual intelligence of high and low class XII SMAN I Kediri, with the formulation of the problem 1) What is the level of intelligence spiritual students ? 2) How Self Control students who have high spiritual intelligence? 3) How Self Control students who have low spiritual intelligence? 4) Do Self Control students who have high spiritual intelligence is stronger than the Self Control students who have low spiritual intelligence? This study uses a mixed method approach. The data collection was conducted by questionnaire, documentation, interviews and observation. The population of this research is class XII student of SMAN I Kediri. Sampling starts with random sampling techniques on Muslim students in class XII and generalized according to the level of intelligence Spiritual owned. Statistical data analysis with independent t-test formula. The research sample for the group of students who have Spiritual intelligence is as many as 152 students were taken based on Table Krejcie for error rate () of 0.05 of the total students totaling 250 students, from 152 students after given a rating based on spiritual intelligence instrument Â then found the sample group students who have high spiritual intelligence as much as 21 sample groups of students as well as students who have high spiritual intelligence as many as 48 students. The results showed that: There is a significant difference between self-control students who have high spiritual intelligence and lower in class XII SMAN I Kediri, with the ratio of the average score - average self control 132.05: 116.65 15.40 difference. The results of the analysis of statistical calculation through a formula independent t-test result value Sig (2-tailed) 0,000 less than the alpha value of Â () 0.05, and concluded that self-control students who have high spiritual intelligence is different from the students who have the self control low spiritual intelligencein class XII SMAN I Kediri year 2013/2014.